2016
DOI: 10.18052/www.scipress.com/ilns.53.40
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variability of Carbon Monoxide (CO) in the Ambient Environment of IMO State, Nigeria

Abstract: The air quality of four areas in Imo State with a total of twenty two locations was monitored for a period six months with respect to CO level using Gasman air monitor (Crowcon Instruments Ltd, England. The air quality monitoring was conducted in the morning, afternoon and evening hours within dry and wet seasons in order to elucidate the variability of this atmospheric pollutant in the study locations. The results obtained showed significant variation of the air pollutant in the morning, afternoon and evening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…CO is a trace gas, emitted due to incomplete combustion of fossil fuel and reaction among oxidation of hydrocarbons, volatile organic compounds, and methane, also from the vehicle, industrial hubs, open burning as well as aircraft emission (Jaffe 2012 ) and wood fires (Aneja et al 2001 ; Gaur et al 2014 ; Njoku et al 2016 ). The diurnal pattern varies highly based on human activities in urban centres (Jaffe 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…CO is a trace gas, emitted due to incomplete combustion of fossil fuel and reaction among oxidation of hydrocarbons, volatile organic compounds, and methane, also from the vehicle, industrial hubs, open burning as well as aircraft emission (Jaffe 2012 ) and wood fires (Aneja et al 2001 ; Gaur et al 2014 ; Njoku et al 2016 ). The diurnal pattern varies highly based on human activities in urban centres (Jaffe 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…1. Variation was categorized according to previous publications (Njoku et al 2016;Opara et al 2016). Health risk assessment was also carried out to determine the tendency of cancer risk due to the PAHs.…”
Section: Discussionmentioning
confidence: 99%
“…They could be emitted from processes that occur naturally such as volcanic eruptions, biomass combustion, and diagenetic processes (Wang et al 2011). Atmospheric deposition could contribute to high PAH concentrations in areas considered unpolluted by virtue of the economic and other anthropogenic activities in such areas (Marr et al 2006;Tian et al 2009;Opara et al 2016;Njoku et al 2016;Ibe et al 2020). In addition, the low elevation of the area (control) as well as high permeability and porosity of the Benin Formation may have contributed to the increased concentration of PAHs (Onyeagocha 1980;Ibe et al 2020;Ejiogu et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial concentration pattern of ozone can be represented as Victoria>Ballygunge>RabindraSarovar>FortWilliam>Padmapukur>RabindraBharati>Jadavpur>Ghusuri in the prelockdown phase and Victoria>Ballygunge>RabindraSarovar>Padmapukur>Fort William>RabindraBharati>Jadavpur>Ghusuri during lockdown phase. CO is a trace gas, emitted due to incomplete combustion of fossil fuel and reaction among oxidation of hydrocarbons, volatile organic compounds and methane, also from the vehicle, industrial hubs and wood res (Aneja et al 2001;Gaur et al 2014;Njoku et al 2016). National Green Tribunal (2019) reported that street food stalls on footpaths use charcoal, dump cake and other materials as fuel are the sources of severe pollution.…”
Section: Observed Concentration Of the Air Pollutantsmentioning
confidence: 99%